A Direct Comparison of Patients With Hereditary and Sporadic Pancreatic Neuroendocrine Tumors: Evaluation of Clinical Course, Prognostic Factors and Genotype–Phenotype Correlations - Soczomski, Przemysław; Jurecka-Lubieniecka, Beata; Krzywon, Aleksandra; Cortez, Alexander Jorge; Zgliczynski, Stanisław; Rogozik, Natalia; Oczko-Wojciechowska, Małgorzata; Pawlaczek, Agnieszka; Bednarczuk, Tomasz; Jarzab, Barbara (Frontiers in Endocrinology, 2021)
Introduction Pancreatic neuroendocrine tumors (PNETs) in hereditary syndromes pose a significant challenge to clinicians. The rarity of these syndromes and PNETs itself make it difficult to directly compare them with sporadic PNETs. Despite research suggesting differences between these two entities, the same approach is used in hereditary and sporadic PNETs. Methods We included 63 patients with hereditary PNET (GpNET) and 145 with sporadic PNET (SpNET) in a retrospective observational study. Clinical and genetic data were collected in two Polish endocrine departments from January 2004 to February 2020. Only patients with confirmed germline mutations were included in the GpNET cohort. We attempted to establish prognostic factors of metastases and overall survival in both groups and genotype–phenotype correlations in the GpNET group. Results Patients with GpNET were younger and diagnosed earlier, whereas their tumors were smaller and more frequently multifocal compared with patients with SpNET. Metastases occurred more frequently in the SpNET group, and their appearance was associated with tumor size in both groups. GpNET patients had longer overall survival (OS). OS was affected by age, age at diagnosis, sex, grade, stage, tumor diameter, occurrence and localization of metastases, type of treatment, and comorbidities. In the MEN1 group, carriers of frameshift with STOP codon, splice site, and missense mutations tended to have less advanced disease, while patients with mutations in exon 2 tended to have metastases more frequently. Conclusions Direct comparisons of GpNET and SpNET demonstrate significant differences in the clinical courses of both entities, which should force different approaches. A larger group of patients with GpNET should be assessed to confirm genotype–phenotype correlations.